Infodemic insights: Mapping COVID-19’s digital discourse in Romania - Sǎvescu Andrei Răzvan; Mazurencu-Marinescu-Pele Miruna; Conda Alexandra-Ioana; Bolovǎneanu Vlad; Pele Daniel Traian (Management şi Marketing)
The coronavirus disease 2019 (COVID-19) pandemic, while primarily a global health crisis, also triggered an infodemic – a surge of information ranging from accurate to misleading, significantly shaping public perceptions and behaviors through social networks. This study analyzes the COVID-19 infodemic in Romania using social media datasets from CrowdTangle, integrating text analysis, sentiment analysis, and social network analysis to examine pandemic-related discourse, identify key themes, and trace the spread of various types of information. The findings provide insights into how the infodemic influenced collective responses, offering strategies for managing information flow during health crises. This study highlights the crucial role of social media in shaping public awareness and underscores the need for effective communication strategies to counter misinformation and improve public understanding in future emergencies.